Ten calls to action to increase accountability for nutrition actions - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
As we move into the era of the Sustainable Development Goals (SDGs), the world faces many seemingly intractable problems. Malnutrition should not be one of them. Countries that are determined to make rapid advances in malnutrition reduction can do so. If governments want to achieve the SDG target of ending all forms of malnutrition by 2030, they have clear pathways to follow. There are many levers to pull, and this report provides abundant examples of countries that have done so.